International Monetary Fund Annual Report 1960. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1960)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1960. The report highlights that the year ended April 1960 showed a continued upswing in world industrial activity and an increase in world trade. Industrial production in 1959 was greater by 10 percent than in the recession year of 1958, and the value of world trade increased by 6 percent, both increases being more or less continuous from about the middle of 1958.